Description Regarding the Influence of Teacher Qualifications and Competence on Early Childhood Learning Achievement - Astiwi, Wuri; Siswanto, Deny Hadi; Suryatama, Handika (Asian Journal of Applied Education (AJAE), 2024)
This research examines the impact of teacher qualifications and competencies on children's academic achievement in Early Childhood Education (ECE) schools. Using quantitative methods, data were collected from 100 children in ten ECE schools. Teacher qualifications were evaluated based on formal education and training, while competencies were assessed through evaluations and feedback. Children's academic achievements were measured using academic and socio-emotional development assessments. Results show a significant positive correlation between teacher qualifications and competencies and children's achievements. Teachers with higher qualifications and better competencies have students with higher academic and socio-emotional achievements. The study highlights that interpersonal competencies, such as communication skills and empathy, greatly impact children's socio-emotional development, while academic qualifications more strongly influence academic outcomes.